Transforaminal lumbar interbody fusion (TLIF) surgery: A finite element analysis of open and minimally invasive approach on L4-L5 segment - Kishore Pradeep; Bidyut Pal; Kaushik Mukherjee; Gautam M. Shetty (Heliyon)
Background: To compare the effect of minimally invasive and open transforaminal lumbar interbody fusion (TLIF) approaches in fusing the L4-L5 segment and predicting the potential risk of adjacent segment degeneration (ASD). Methods: A computed tomography scan image was processed and the three-dimensional model of the L1-L5 spine was reconstructed. The minimally invasive and Open TLIF finite element models were constructed. The models were analyzed using an axial compressive load (500 N) and physiological movements like flexion, extension, and lateral bending with a combined load and moment (150 N and 10 Nm). The ranges of motion (ROM), stress-strain distributions on the L4-L5 implanted segment and cranial adjacent soft structures were compared with the intact model. Results: A substantially comparable drop in ROM was observed for both models due to implantation. The stress and strain distributions on the implanted segment of both models were nearly identical. The peak strain on the L4-L5 was higher than 0.007 for both models. The maximum stress and strain observed on adjacent segment soft structures, except for the annulus fibrosus of both the implanted models, were substantially higher than the intact structures. Conclusions: The open and MI-TLIF approaches are effective in reducing ROMs. However, the higher stress and strain on the L4-L5 segment indicate the chances of bone failure. The higher stress and strain on the adjacent segment soft structures indicate the potential risk of ASD in both models. However, considering the lower intrusive nature of the MI-TLIF technique, it might be favoured over Open TLIF.